Avoidance behaviour in laboratory domestic mice (Mus musculus) and Norway rats (Rattus norvegicus) towards predator odours - Adduci, Luciana Beatriz (2021)
Mus musculus and Rattus sp. are considered pest species because they reach high densities in urban areas, crop fields and food storage and productive systems such as breeding farms and orchards. Their control relies mainly on rodenticide application, but the effectiveness of this application is reduced due to behavioural responses and resistance. Novel methods are based on the use of chemical signals as odours that may be attractants, repellents or may reduce the reproductive success of pest species. The aim of this paper is to study the aversive effect of TMT, cat urine and cat fur body odour on predator-inexperienced Mus musculus and Rattus norvegicus under laboratory conditions. The experimental apparatus comprised three boxes connected by PVC pipes in a linear arrangement. In lateral boxes, odour sources or distilled water were introduced, while animals were placed in the central box at the beginning of the experiment. Rats showed freezing behaviour, reduced visits in the presence of TMT and cat body odour. Mice reduced their visits with cat body and and cat urine. This study provide evidence of the usefulness of using fear responses as a way to control rodents pests, which must be adapted to the environment and species to be applied